FATIMA MERNISSI DAN SIMBOL PERLAWANAN TERHAPAD HADITH- HADITH MISOGINIS (Kajian Terhadap Pandangan Fatima Mernissi mengenai Hadith “Wanita, Anjing dan Keledai Membatalkan Shalat ” riwayat Abū Hurairah) - Yunita, Yunita (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: Born in the patriarkhial community, where women are forbidden to take a part in the political dynamics. Where their society-live is pressed with the extreme limitation, and their liberation of thingking and action is prisoned, Fatima Mernissi was used to life in the light of her critism against this discriminating cultures and religions. She was one of Moeslem scholars who took a hard line concerning the mysoginical h}adith. This article is written down to elaborate how Fatima understood h}adith, on what ideas he built his theory of understanding, and how the spirit of women freedom brought by her, determined her inclination in the studies on h}adits. Keywords: H{adith Misoginis, Pembebasan Perempuan, Anjing dan  Makna Literal